2019
DOI: 10.3892/ol.2019.10677
|View full text |Cite
|
Sign up to set email alerts
|

Role of EphA2‑PI3K signaling in vasculogenic mimicry induced by cancer‑associated fibroblasts in gastric cancer cells

Abstract: Although erythropoietin-producing human hepatocellular receptor A2 (EphA2) signaling serves an important role in the tumor microenvironment, its contribution to vasculogenic mimicry (VM) formation in gastric cancer cells remains unclear. The aim of the present study was to investigate the role of EphA2 in VM formation induced by cancer-associated fibroblasts (CAFs). The conditioned medium of CAFs (CAF-CM) was prepared from 12 patients with gastric adenocarcinoma. VM was evaluated by the number of tubules and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…However, the relationship between CAFs and VM formation has rarely been reported. Recently, some studies have con rmed that CAFs can promote VM formation in some tumors, such as HCC [30] and gastric cancer [31,32]. In this study, we observed that GCAFs can promote VM formation and tumor growth of GBC in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, the relationship between CAFs and VM formation has rarely been reported. Recently, some studies have con rmed that CAFs can promote VM formation in some tumors, such as HCC [30] and gastric cancer [31,32]. In this study, we observed that GCAFs can promote VM formation and tumor growth of GBC in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, it was reported that CAFs can promote VM formation in some malignant tumors, such as hepatocellular cancer (HCC) [30] and gastric cancer [31,32]. However, so far, the mechanism of VM formation is not clear, and the relationship between gallbladder cancer-associated broblasts (GCAFs) and VM formation in GBC has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between CAFs and VM formation has rarely been reported. Recently, some studies have con rmed that CAFs can promote VM formation in some tumors, such as HCC [21] and gastric cancer [41,42]. In this study, we observed that GCAFs can promote VM formation and tumor growth of GBCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 61%
“…At present, the mechanism of CAFs promoting tumor VM formation is not clear. It was reported that CAFs promoted VM formation in HCC by paracrine TGF-β and SDF1 [21]; CAFs-derived HGF promoted vascularization in gastric cancer via PI3K/AKT and ERK1/2 signaling [41]; CAFs induced vasculogenic mimicry in gastric cancer cells through the role of EphA2-PI3K signaling [42]. In order to explore the underlying molecular mechanism of GCAFs promoting VM formation in GBC, in view of aforementioned microarray analysis results, we found that among 154 VM-related genes, NOX4, JAK and STAT3 are involved in VM formation of GBC.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that CAF-CM-induced VM formation was blocked by EphA2inhibitor and PI3K-inhibitor. In conclusion, CAFs regulate VM formation via EphA2-PI3K signaling in gastric cancer cells [79] (Fig. 2).…”
Section: Tumor-associated Fibroblastsmentioning
confidence: 80%